Hydrodynamic re-examination of underwater non-propulsive phase in front crawl - Koga, D.; Homoto, K.; Tsunokawa, T.; Takagi, H. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to re-examination of the hand propulsive force (FP) during the entry and catch (EC) phase in a stroke of front crawl. The EC phase was defined as non-propulsive phase (Collet et al., 2000), which is until a hand starts moving backwards after it enters the water and moves forward. The other phases in the stroke was defined as propulsive phase. Twelve male swimmers performed a 20-m front crawl with maximal effort. For estimatinng the FP, six pressure sensors were attched on their right hand and trials were recorded by three-dimentional motion capture system. We calculated %EC that was the ratio of the mean FP in the EC phase to the mean FP in the propulsive phase. As a result, the mean FP in the EC phase was 22.4 ± 12.9 N and the %EC was 29.1%. Therefore, it was considered the EC phase is propulsive phase even though the hand moves forward.